Rainfall Characteristics Over Kenyir Dam Catchment Under AR5 Climate Change Scenarios - Rahmat, Siti Nazahiyah; Tukimat, Nurul Nadrah Aqilah; Kasmin, Hartini; Muhammad Hanafi (International Journal of Integrated Engineering, 2025)
In this study, the Coupled Model Intercomparison Project Phase 5 (CMIP5) dataset namely CanESM2, a Canadian Earth System Model was used to assess the potential changes of rainfall characteristics over the Kenyir dam catchment. The changes were computed for two future time slices (2025–2055 and 2056–2085) relative to the reference period (1988–2017) under three Representative Concentration Pathways (RCPs; RCP2.6, RCP4.5 and RCP8.5). For comparison purposes, climate change data was also obtained from National Hydraulic Research Institute of Malaysia (NAHRIM). NAHRIM climate data are based on GCMs adopting the Special Report on Emission Scenarios (SRE) scenarios in the AR4. The three selected GCMs were CCSM3, ECHAM5 and MRI-CGCM2.3.2. The simulated rainfall patterns generally resemble those in the historical observations. However, the CCSM, ECHAM and MRI produce lower monthly rainfall, while generally CanESM2 simulations produce monthly rainfall that are more consistent with the historical observations for RCP2.6, RCP4.5 and RCP8.5. The projected future climate rainfall by the CanESM2 suggest slightly decreasing of total rainfall over the Kenyir dam catchment due to the global warming. The largest decrement appears to be in January and February. The analysis of historical daily rainfall characteristic has suggested remarkable changes in the hydroclimatic regimes over this catchment. Understanding of such changes allow better risk assessment and mitigation planning for water security.